Relationship between 28-days Compressive Strength and Compression Toughness Factor of Ultra High Performance Concrete Using Design of Experiments. (2016) - Mosaberpanah, Mohammad Ali; Eren, Ozgur
Abstract: Usually, a material of higher strength does not necessarily indicate in a higher structural performance. While a higher energy absorbing material usually expresses higher structural performance when failure happens. This study aims at finding the relation between 28-days compressive strength and Compression toughness factor of Ultra High Performance Concrete (UHPC) using varying range of five variables which include; Steel Fiber, Silica fume (SF), Cement 42.5, Superplasticizer (SP), and water to cemetiotious ratio (w/c) by Design of Experiments (DOE) methodology. The results shows the significant relationship between the Compression toughness factor and 28 days compressive strength of UHPC. The model is valid for the mixes made with 1.0 sand, 0.15-0.30 silica fume amount, 0.70-1.30 cement amount, 0.10- 0.20 steel fiber, 0.04- 0.08 superplasticizer (all values are by aggregate weight mass) and 0.18- 0.32 water to cementitious ratio.